Wednesday

April 16, 2014

April 16, 2014

Posted by **Jackie** on Tuesday, April 22, 2008 at 8:25pm.

(2x^1/2) * (6x^2 - x^1/2)

Here it is in words to make the equation clearer

(two x to the one half power) multiplied by (6x squared minus x to the one half power)

**Related Questions**

How do I do this.?(Math.) - Use the Substitution method to solve the system of ...

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

Math - How would I solve the quadratic equation: 2x^2 + 6x = 0 I would factor ...

Math 3 - If you want to be eligible for partial credit, please show your work. ...

Algebra - I'm not sure if anyone saw my question yesterday, but here it is again...

Math - i forgot how to solve problems like this... 2x^2-18x=0, x^2=6x+7, 6y^2+5y...

Math - Solve 2x-y+3z=8 x-6y-z=0 -6x+3y-9z=24 Did you notice that your third ...

Maths - 1) Factorise x2 -6x +8 (the 2 is squared) 2) Hence solve this equation: ...

algebra - - #21 -can you help me solve this equation: 3x^2 (2x - 2) i keep ...

math - 2x+4(1-x)=11+5x 2x+4-4x=11+5x 6x+4=11+5x 6x=7+5x x=7 i think this is it x...